2017
DOI: 10.1021/acs.cgd.7b01085
|View full text |Cite
|
Sign up to set email alerts
|

A Metal–Organic Framework to CuO Nanospheres of Uniform Morphology for the Synthesis of α-Aminonitriles under Solvent-Free Condition along with Crystal Structure of the Framework

Abstract: Herein, we have reported the synthesis, crystal structure, thermogravimetric property, and photoluminescence activity of a new Cu-based metal organic framework (MOF): {[Cu2(2,5-pdc)2­(ald-4)­(H2O)2]­·3H2O,MeOH} n (where 2,5-pdc = 2,5-pyridine-dicarboxylate, ald-4 = aldrithiol-4) along with catalytic activity of CuO nanoparticles (Cu-NPs) derived from the MOF for green synthesis of organic molecules having biological relevance. The regular arrangement of metal centers and the presence of oxygen and carbon in m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 16 publications
(8 citation statements)
references
References 76 publications
0
8
0
Order By: Relevance
“…The XRD pattern showed that this compound is crystalline, and the UiO-66-Pyca-CuO pattern closely resembled that of UiO-66-NH 2 , although differences in peak intensities were observed. This is associated with the unique morphology of the flower-like CuO nanosheets (Figure c). , …”
Section: Resultsmentioning
confidence: 91%
“…The XRD pattern showed that this compound is crystalline, and the UiO-66-Pyca-CuO pattern closely resembled that of UiO-66-NH 2 , although differences in peak intensities were observed. This is associated with the unique morphology of the flower-like CuO nanosheets (Figure c). , …”
Section: Resultsmentioning
confidence: 91%
“…Although 4,4 0 -dipyridyldisulfide (L 0 ) has been widely reported as a donor towards a variety of metal ions (Sarkar et al, 2016;Zheng et al, 2022Zheng et al, , 2023Singha et al, 2018), its reactivity towards halogens or interhalogens has been only marginally explored (Wzgarda-Raj et al, 2021;Coe et al, 1997). An example is provided by 4,4 0 -(disulfanediyl)dipyridinium pentaiodide triiodide (CSD code OXAFIF; Wzgarda-Raj et al, 2021) where the cation H 2 L 02+ is counterbalanced by a polyiodide built up of interacting I 3 À and I 5 À ions.…”
Section: Chemical Contextmentioning
confidence: 99%
“…Reusability of the catalyst was demonstrated since no loss of activity was detected after 10 runs. Saha et al prepared CuONPs by thermal decomposition of a previously synthesized two-dimension copper organic framework (2D-(Cu)COF) [170]. 2D coordination polymer was characterized by single-crystal XRD prior decomposition.…”
Section: Multi-step Redox Reactionsmentioning
confidence: 99%